2023
DOI: 10.1002/jmv.28658
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and phospholipids: Friends and foes during infection

Abstract: Viruses have evolved complex and dynamic interactions with their host cells to enable viral replication. In recent years, insights have been gained into the increasingly important role of the host cell lipidome in the life cycle of several viruses. In particular, viruses target phospholipid signaling, synthesis, and metabolism to remodel their host cells into an optimal environment for their replication cycle. Conversely, phospholipids and their associated regulatory enzymes can interfere with viral infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 107 publications
(232 reference statements)
0
3
0
Order By: Relevance
“…The biological importance of membrane lipids has long been recognised, both as barriers to infection and, once cleaved, as circulating or locally acting modulators of the immune response to pathogens. [1][2][3] While perturbation of the serum lipidome by infections is well documented, [4][5][6][7][8] attention has focused on high abundance lipids such as phospholipids, ceramides and sphingomyelins. This has been true also in COVID- 19 where the high abundance lipidome has been implicated in prognosis, 9 pathogenesis 10 and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The biological importance of membrane lipids has long been recognised, both as barriers to infection and, once cleaved, as circulating or locally acting modulators of the immune response to pathogens. [1][2][3] While perturbation of the serum lipidome by infections is well documented, [4][5][6][7][8] attention has focused on high abundance lipids such as phospholipids, ceramides and sphingomyelins. This has been true also in COVID- 19 where the high abundance lipidome has been implicated in prognosis, 9 pathogenesis 10 and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…We super-resolved here for the first time within the context of human clinical FFPE tissue the multiple nuclear antigens, specifically the molecular anatomy of NS and its associated nPI(4,5)P2 pool. Nanoscale protein and lipid interactions execute specific cellular functions and their impairment or hijacking by pathogens leads to the development and progression of disease (Rattay et al, 2023). Here, we quantitatively showed that, compared with healthy skin nuclei, the staining of SON + NS-associated pool of nPI(4,5)P2 is increased in nuclei in HPV-induced wart.…”
Section: Discussionmentioning
confidence: 72%
“…The biological importance of membrane lipids has long been recognized, both as barriers to infection and, once cleaved, as circulating or locally acting modulators of the immune response to pathogens (1)(2)(3). While perturbation of the serum lipidome by infections is well-documented (4 -8), attention has focused on high abundance lipids such as phospholipids, ceramides and sphingomyelins.…”
Section: Introductionmentioning
confidence: 99%